Pemenuhan kebutuhan informasi dalam perkumpulan kaum suku Jambak Dt. Maruhun Basa Kabupaten Agam - Fadhila Nurul Husna Zalmi (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
Information need is a basic of human need. That is, since people can communicate. Meeting the information needs of a person will have a different way of fulfilling their curious race. Information needs closely related to the communication made by someone with others. The research was conducted at a gathering of the Jambak tribe of Datuak Maruhun Basa at Balai Panjang III Kampung Kabupaten Agam. This meeting was conducted by the children, nephews, grandchildren, and Datuak Maruhun Basa descendants from the area of Balai Panjang III Kampung Kabupaten Agam. This research uses descriptive qualitative research method by conducting observations and in-depth interviews with Datuak Maruhun Basa and several members of the Jambak tribe meeting. The activity of this Jambak tribe meeting aims to build together the members of the tribe Jambak. So it can be concluded that in a meeting conducted by members of the tribe Jambak Dt. Maruhun Basa is able to meet the information needs of each member. Meeting the information needs they get with all activities carried out at each meeting.